Ð˜Ð·ÑƒÑ‡ÐµÐ½Ð¸Ðµ Ð²Ð¾Ð·Ð¼Ð¾Ð¶Ð½Ð¾ÑÑ‚Ð¸ Ð±Ð¸Ð¾ÑÑ‚Ð¸Ð¼ÑƒÐ»ÑÑ†Ð¸Ð¸ Ð·Ð°Ð¶Ð¸Ð²Ð»ÐµÐ½Ð¸Ñ Ð¾Ð¶Ð¾Ð³Ð¾Ð²Ñ‹Ñ… Ñ€Ð°Ð½ ÑÑƒÑÐ¿ÐµÐ½Ð·Ð¸ÐµÐ¹ ÑÐ²ÐµÐ¶ÐµÐ²Ñ‹Ð´ÐµÐ»ÐµÐ½Ð½Ñ‹Ñ… Ð¸ ÐºÑ€Ð¸Ð¾ÐºÐ¾Ð½ÑÐµÑ€Ð²Ð¸Ñ€Ð¾Ð²Ð°Ð½Ð½Ñ‹Ñ… Ð¼ÐµÐ·ÐµÐ½Ñ…Ð¸Ð¼Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÑÐ¼Ð±Ñ€Ð¸Ð¾Ð½Ð°Ð»ÑŒÐ½Ñ‹Ñ… ÐºÐ»ÐµÑ‚Ð¾Ðº - Revenko, E. B.; Petrenko, A. Yu.; Goncharuk, E. I.; Volkova, N. A.; Petrenko, T. F.; Volina, V. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2004)
The influence of both freshly isolated and cryopreserved mesenchymal embryonic cells (MEC) on reparative process activity in a burn wound was studied. Obtained results have shown the viable freshly isolated either cryopreserved embryonic cells are capable of accelerating the wound defect re-epithelization processes. No rough scar during the skin recovery process and cosmetic cicatrix tissue formation are peculiar for their effect.